2009
DOI: 10.1128/ec.00329-08
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudouridine Synthase Homologue Is Critical to Cellular Differentiation inToxoplasma gondii

Abstract: Toxoplasma gondii is a haploid protozoan parasite infecting about one in seven people in the United States. Key to the worldwide prevalence of T. gondii is its ability to establish a lifelong, chronic infection by evading the immune system, and central to this is the developmental switch between the two asexual forms, tachyzoites and bradyzoites. A library of mutants defective in tachyzoite-to-bradyzoite differentiation (Tbd ؊ ) was created through insertional mutagenesis. This library contains mutants that, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…We note that these TgPUS1-deficient parasites are insertional mutants (TBD5, isolated by Singh et al 2002 and characterized by Anderson et al 2009), rather than TgPUS1 knockouts. Furthermore TgPUS1-deficient parasites incubated under bradyzoite conditions for 84 h are not able to differentiate; therefore, TgPUS1-deficient "bradyzoites" express subsets of both tachyzoite and bradyzoite markers (Anderson et al 2009 and data not shown).…”
Section: Psi-seq Identifies Evolutionarily Conserved Sites Of Pseudoumentioning
confidence: 92%
See 2 more Smart Citations
“…We note that these TgPUS1-deficient parasites are insertional mutants (TBD5, isolated by Singh et al 2002 and characterized by Anderson et al 2009), rather than TgPUS1 knockouts. Furthermore TgPUS1-deficient parasites incubated under bradyzoite conditions for 84 h are not able to differentiate; therefore, TgPUS1-deficient "bradyzoites" express subsets of both tachyzoite and bradyzoite markers (Anderson et al 2009 and data not shown).…”
Section: Psi-seq Identifies Evolutionarily Conserved Sites Of Pseudoumentioning
confidence: 92%
“…We previously reported that a PUS is necessary for differentiation of the parasite Toxoplasma gondii (Anderson et al 2009). This single-celled eukaryote can exist within its human host as fast-growing tachyzoites or as slower-growing encysted bradyzoites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the SRS9 gene or the SAG2CDXY gene locus revealed a phenotype of normal cyst burdens at 4 weeks postinfection, and then reduced cyst burdens were observed later during latent infection (41,55). Disruption of a pseudouridine synthase homologue (PUS1) revealed a phenotype of slightly smaller cyst size and slightly increased cyst burdens (1). Targeted disruption of the heat shock protein BAG1 gene (6,69) resulted in a minor defect in cyst development.…”
Section: Vol 10 2011 Analysis Of Cyst Development and Latent Infectmentioning
confidence: 99%
“…Nine distinct targeted gene deletions (1,6,13,32,38,54,55,57,65,69) have been successfully developed in type II strains since genetic transformation of T. gondii was reported nearly 20 years ago (18,39,61). In contrast, recently reported type I KU80 knockout strains that exhibit highly efficient gene replacement frequencies has significantly accelerated the development of targeted gene deletions (2,3,15,20,23,26,34,37,44).…”
mentioning
confidence: 99%